DISCOURSE ANALYSIS: ANALYSING ADJACENCY PAIRS OF TEACHER AND STUDENTS - Rum Muhammad (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2017)
This research aimed at analyzing the kinds of Adjacency Pairs and their function used by a teacher and the students in the classroom. This research employed a descriptive research method with non-participants observer. The sample of this research was teacher and students of ELC Education Makassar. The data collected through the use of audio recording and then it was transcribed to be analyzed. The study shows that there are five types of Adjacency Pairs found in the teaching process. First, degreeting degreeting pair which functions as an agreement to discontinue the certain conversation. Second, the reasearcher encountered a greeting greeting pair which also a pair that has similar function as the previous pair, an agreement to discontinue the certain conversation. Furthermore, a question refusal pair is also found in this research. It functions as questioning and refusing utterance where there is a questions and then it follows with a refusal. Then, an offer refusal pair can be found during the classroom interaction where there is an offer and the other speaker accepts the related utterance. The last pair is a question answer pair which also occurs in this reasearch. It functions as questioning and answering to the related remark.